Energy transfer from Cr3+ to Nd3+ and NIR luminescence of Nd3+ in lead borate glasses - Pisarska, Joanna (Oficyna Wydawnicza Politechniki Wrocławskiej, 2008)
Energy transfer processes from Cr3+ to Nd3+ and NIR luminescence of Nd3+ ions at 1.06 μm in Cr–Nd co-doped lead borate glasses have been investigated. The spectroscopic investigation indicates that Cr3+ ions are located at strong-field and weak-field sites. Replacing PbO by PbF2 in lead borate glasses slightly influences the energy transfer processes between Cr3+ and Nd3+ and NIR luminescence of Nd3+ ions. The energy transfer process occurs in both oxide and oxyfluoride glass systems, which may be due to the thermally induced population of the 4T2 excited state of Cr3+ ions and the participation of lattice phonons.
Optica Applicata, Vol. 38, 2008, nr 1, s. 203-210
Keywords: optyka; lead borate glasses; Cr3+ and Nd3+ ions; energy transfer; optical properties